A rapidly responsive photochromic hydrogel with high mechanical strength for ink-free printing. Issue 28 (5th July 2018) - Yang, Yongqi; Guan, Lin; Jiang, Haicheng; Duan, Lijie; Gao, Guanghui
Abstract : We report a hydrogel with excellent mechanical strength and rapid photochromism that can be used for ink-free printing. Abstract : Ink-free printing based on photochromism has attracted great attention as a new generation of printing technology. However, the current photochromic materials are limited due to slow response and high cost. In this investigation, a rapidly responsive photochromic hydrogel with high mechanical strength was explored through the introduction of cheap ammonium molybdate into gelatin and hydrophobic associative polyacrylamide. The photochromic hydrogel exhibited excellent mechanical strength of 750 kPa and a rapidly responsive photochromic process of 5 seconds with UV light irradiation. Moreover, the hydrogel could withstand long elongation and high compressive stress with shape recovery ability. The rapid photochromic properties gave hydrogels with fast and easy "printing" performance. More importantly, the "printed" text or pattern in hydrogels could be erased at 70 °C in an oxygen environment. In addition, the hydrogel could be written on in characters by using reducing reagents. Photochromic hydrogels with ink-free printing ability would demonstrate a new design strategy for soft materials with low-cost, rapid response and high mechanical properties.